Expression and purification of hemagglutinin and neuraminidase recombinant protein of avian influenza a virus using immobilised metal affinity chromatography (imac) - Chiang, Goh Wei (Universiti Sains Malaysia, 2016)
Avian influenza A virus is a member of Orthomyxoviridae family. It has an envelope of 120nm in diameter. It has 8 segmented negative-sense RNA. There are two major proteins that play important roles in virus infectivity which are hemagglutinin (HA) and neuraminidase (NA). Influenza A virus are able to undergo antigenic drift and antigenic shift. The gene sequence in the virus is replicated by error-prone RNA polymerase. All these leads to the emergence of new subtype of influenza A virus that expressed different HA and NA glycoprotein. Consequently, the burden of influenza epidemics is approximately 3-5 million cases and results in 300,000-500,000 deaths globally. Thus, conserved region in HA and NA glycoprotein are important as it can be used for future development of universal influenza vaccine (UIV) or detection kit. In this study, the gene that encodes for the conserved regions in HA and NA glycoprotein of avian influenza A virus were expressed using bacterial expressing system. The recombinant sequence were firstly verified and confirmed the sequence from NCBI genebank. pET-47b(+) plasmid that contains synthetic HA and NA gene were transformed into BL21 E.coli strain. The transformed E.coli was induced with IPTG to produce desired HA and NA recombinant proteins. The His-tagged NA and HA protein were purified using immobilized metal affinity chromatography (IMAC). Recombinant protein present in the eluted fraction was further purified by size exclusion method. Purified recombinant protein was dialyzed with PBS to allow refolding back to its native conformation state. In conclusion, recombinant HA and NA were successfully expressed and purified.